A Biocompatible Heterogeneous MOF–Cu Catalyst for In Vivo Drug Synthesis in Targeted Subcellular Organelles. Issue 21 (9th April 2019) - Wang, Faming; Zhang, Yan; Liu, Zhengwei; Du, Zhi; Zhang, Lu; Ren, Jinsong; Qu, Xiaogang
Abstract: As a typical bioorthogonal reaction, the copper‐catalyzed azide–alkyne cycloaddition (CuAAC) has been used for drug design and synthesis. However, for localized drug synthesis, it is important to be able to determine where the CuAAC reaction occurs in living cells. In this study, we constructed a heterogeneous copper catalyst on a metal–organic framework that could preferentially accumulate in the mitochondria of living cells. Our system enabled the localized synthesis of drugs through a site‐specific CuAAC reaction in mitochondria with good biocompatibility. Importantly, the subcellular catalytic process for localized drug synthesis avoided the problems of the delivery and distribution of toxic molecules. In vivo tumor therapy experiments indicated that the localized synthesis of resveratrol‐derived drugs led to greater antitumor efficacy and minimized side effects usually associated with drug delivery and distribution. Abstract : Hit the spot : A copper‐functionalized triphenylphosphonium‐modified metal–organic framework catalyzed localized drug synthesis in mitochondria through a site‐specific copper‐catalyzed azide–alkyne cycloaddition (CuAAC) reaction (see picture). This system has wide applicability for the in situ synthesis of drugs with good biocompatibility and has unique advantages for improving the efficacy of active drugs and avoiding side effects.